2013
DOI: 10.1208/s12248-013-9550-y
|View full text |Cite|
|
Sign up to set email alerts
|

Squarticles as a Lipid Nanocarrier for Delivering Diphencyprone and Minoxidil to Hair Follicles and Human Dermal Papilla Cells

Abstract: Abstract. Delivery of diphencyprone (DPCP) and minoxidil to hair follicles and related cells is important in the treatment of alopecia. Here we report the development of "squarticles," nanoparticles formed from sebum-derived lipids such as squalene and fatty esters, for use in achieving targeted drug delivery to the follicles. Two different nanosystems, nanostructured lipid carriers (NLC) and nanoemulsions (NE), were prepared. The physicochemical properties of squarticles, including size, zeta potential, drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…11 We had previously developed the nanoemulsions, which are termed squarticles, that contain squalene as the lipid cores and Pluronic F68/phosphatidylcholines as the emulsifiers for enhancing anti-alopecia drug uptake in hair follicles. 12 Squalene is a polyunsaturated hydrocarbon with a lipophilic character and high biocompatibility. This nonpolar compound is reported to increase the elimination of xenobiotics due to its affinity to lipophilic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…11 We had previously developed the nanoemulsions, which are termed squarticles, that contain squalene as the lipid cores and Pluronic F68/phosphatidylcholines as the emulsifiers for enhancing anti-alopecia drug uptake in hair follicles. 12 Squalene is a polyunsaturated hydrocarbon with a lipophilic character and high biocompatibility. This nonpolar compound is reported to increase the elimination of xenobiotics due to its affinity to lipophilic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, specific means of opening HF gain importance when targeted therapeutic approaches aim at exploiting the entire infundibular volume and delivering compounds to a maximum of HF in a defined skin area. Among chemical methods, hexane, ethanol or detergents have been successfully applied to open the HF orifices [12]. Also, physical means which do not require special equipment represent interesting approaches.…”
Section: How To Improve Transfollicular Drug Delivery?mentioning
confidence: 99%
“…Editorial drug specific accumulation in the HF infundibulum and create persistent levels of drug in the sebaceous gland [15]. Also, particle-based formulations of minoxidil have been tested for the treatment of androgenetica alopecia [12];…”
Section: Clinical Applications For the Transfollicular Administrationmentioning
confidence: 99%
“…2 To elevate these indices, last researches have focused on developing more efficient formulations, i.e., formulations capable of targeting the active compound to hair follicles and sustaining its release. 3 For this, solid lipid nanoparticles, 4 penetration enhancer-containing vesicles 5 and squarticles nanoparticles, formed from sebum-derived lipids, 6 have been proposed. Although many studies have indeed demonstrated improved skin permeation, it is important to consider that minoxidil, a pyridine-derivative, is a potent antihypertensive agent; hence, dermal exposure and a consequent systemic effect should be avoided to minimize adverse side effects.…”
Section: Introductionmentioning
confidence: 99%